KEDUDUKAN DAN PERAN PEREMPUAN SEBAGAI KEPALA KELUARGA MENURUT HUKUM ISLAM (Studi terhadap Kelompok Pemberdayaan Perempuan Kepala Keluarga-PEKKA di Kabupaten Asahan) - Nawir Yuslem, Sukiati, Andri Nurwandi, (AT-TAFAHUM: Journal of Islamic Law, 2018)
Abstract: The role of women is increasingly widespread, one of them being the role of substitute as the backbone of the family or the head of the family. Some of the women who played this role received a negative response from the community because of taboo. This happens because the majority of people still understand that women can only play a role in domestic matters. Unlike in Asaha Regency there are groups of women as family heads (PEKKA). This role is in conflict with KHI and Law no. 1 year 74 states that "men as heads of families and women housewives" then from this paper the author tries to examine through the perspective of Islamic law in order to know the role of women as heads of families, the implementation of duties as female head of household and the success of women as family heads according to Islamic law perspective. This study is a field research (field research) conducted by a qualitative approach method. The nature of the research used in this thesis is descriptive analytic. The data source of this study consists of primary data and secondary data. Primary data was collected from research informants, by conducting interviews and observations, while secondary data is obtained through documentation studies. From the results of the study it can be concluded that the role of women as family heads in the Asahan PEKKA group is the main breadwinner to take decisions and policies for various reasons. As well as acting as a protector for the family and doing the work of the husband, helper, spouse.Keywords: Women, family heads, PEKKA, Asahan,